The Influence of Learning Style Utilization towards Experimental Learning Outcomes of Cadets in Boarding School / Vocational Education - Suprapto, Yuyun; Nurlaela, Luthfiyah; Masitoh, Siti (Journal of Education, Health and Sport, 2019)
Learning style is the way individuals begin to concentrate on, process, internalize, and remember new and difficult academic information or skill. Learning styles or human learning modalities generally consist of visual, auditory and kinesthetic learning styles which are all related to the eye-brain. Although most humans have access to all three learning style modalities, but generally humans tend to be one of the learning modalities that stand out as a vehicle for learning, processing and communication. This research was related in order to investigate learning outcomes on experimental learning through the use of each lerning style in boarding school education. Boarding school is an educational institution where students not only study, but they live and live together in the institution. The research instrument used were questionnaires and tests, while the data analysis used two ways of ANOVA. The statistical analysis showed that there was difference learning outcomes in Electronica Solid State Subject among experimental learning with CBT and analog experimenter and each learning style. Furthermore, there is no influence of learning styles on student learning outcomes.